All-inorganic metal halide perovskite nanostructures : from photophysics to light-emitting applications - Wang, Yue (2019)
All-inorganic metal halide perovskite nanostructures (IHPNs) have sparked intense research interest by virtue of the superior optical properties and the cost-effective synthesis. Since the first report in 2015, striking development of IHPNs has been witnessed in terms of fabrication strategy, optical characterization, and optoelectronic applications. In this review article, we begin with a brief survey of the mainstream fabrication routes. The emphasis will be put on the understanding of the photophyscis of IHPNs including the electronic structures, steady-state and transient absorption and emission, nonlinear optical properties and representative exotic photophysical phenomena. Afterwards, we summarize the light-emitting applications of IHPNs in lasers and light-emitting diodes. Finally, the challenges and a perspective of the future development of IHPNs will be presented.